Evaluasi Kinerja Simpang Bersinyal Jalan Pahlawan – Raden Saleh Sarif Bustaman di Bogor Jawa Barat - Dwi Bangkit Prakoso; Sutoyo Sutoyo; Tri Sudibyo (Departemen Teknik Sipil dan Lingkungan, IPB University, 2019)
Signaled intersection of Pahlawan steet and Raden Saleh Sarif Bustaman street is one of the main streets in Bogor. This intersection has 3-arm approaches namely Pahlawan Street at East, Raden Saleh Sarif Bustaman Street at North, and Empang Street at West. Highest traffic on weekend is 11653 units/hour or 5087 SMP/hour which occur between 5.20-7.20 pm. Pahlawan - Raden Saleh Sarif Bustaman street obtained inconsistent time cycle of APILL and size of approach dimension which resulted in intersection with high saturated degree. The saturation degree of the intersection of the eastern approaches was 0.75 which meant that this value was same with the standard value in MKJI 1997 which is 0.75. This meant that the performance of intersection capacity was already saturated. The high saturation degree of the intersection resulted in a low level of service level and was classified as, service level E with the intersection delay 45 seconds/SMP. Scenario II is the best alternative scenario for intersections, with the addition of road or lane widening, so the intersection capacity of the eastern, northern and western approaches were 3931, 5066 and 4562 SMP/hour respectively. The average intersection delay became to 9 seconds / SMP, and classified as service level B.Key words: capacity, intersection, intersection delay, service level